(untitled) (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This research explores customer churn and retention in Indonesia’s competitive electronic retail sector, focusing on Eraspace, a digital loyalty app by PT EraX. Despite a structured, incentive-based program, the app faces high churn rates, indicating deeper strategic issues. Using a quantitative survey of 164 participants (active, churned, and non-users), the study analyzes factors like perceived value, user experience (UX), satisfaction, and engagement, employing SEM-PLS for analysis. Findings show that perceived value and UX significantly influence customer satisfaction, but satisfaction and engagement do not reduce churn intention. Key churn drivers include low perceived program benefits, poor UX during point redemption, and weak emotional ties to the brand. A SWOT and QSPM analysis prioritized strategies such as integrating AI and data analytics for personalized loyalty experiences, gamification to boost emotional engagement, and redesigning UX—especially in reward redemption. The study bridges a gap between satisfaction and loyalty by emphasizing emotional engagement at digital touchpoints. It offers practical guidance for PT EraX to enhance Eraspace through UI/UX improvements, personalized rewards, and strategic use of AI. Limitations include reliance on self-reported data and omitted behavioral variables. Overall, the research highlights that reducing churn requires more than satisfaction—it demands emotionally resonant, personalized, and tech-driven experiences.